On the Correctness of Boundary Value Problems for the Two-Dimensional Loaded Parabolic Equation - Attaev, A.Kh.; Ramazanov, M.I.; Omarov, M.T. (Bulletin of the Karaganda University. Mathematics Series, 2022)
The paper studies the problems of the correctness of setting boundary value problems for a loaded parabolic equation. The feature of the problems is that the order of the derivative in the loaded term is less than or equal to the order of the differential part of the equation, and the load point moves according to a nonlinear law. At the same time, the distinctive characteristic is that the line, on which the loaded term is set is at the zero point. On the basis of the study the authors proved the theorems about correctness of the studied boundary value problems.